2022
DOI: 10.21203/rs.3.rs-1369199/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metformin in the management of patients with diabetes and advanced heart failure (HFrEF): a propensity score-matched analysis

Abstract: Background: The role of metformin (MET) in the treatment of patients with advanced HFrEF and type 2 diabetes mellitus (DM) is not firmly established. We studied the impact of MET on metabolic profile, quality of life (QoL) and survival in these patients. Methods: A total of 847 stable patients with advanced HFrEF (57.4± 11.3 years, 67.7% NYHA III/IV, LVEF 23.6± 5.8%) underwent clinical and laboratory evaluation and were prospectively followed for a median of 1126 (IQRs 410; 1781) days for occurrence of death, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Moreover, whereas metformin was not independently associated with clinical outcomes in patients with type 2 DM and heart failure with preserved ejection fraction (HFpEF), it was associated with lower all-cause mortality in the subgroup of patients with poor glycemic control [ 80 ]. In a recent report dealing with diabetic patients with advanced heart failure with reduced ejection fraction (HFrEF), patients treated with metformin demonstrated better quality of life and improved outcomes compared with the patients not receiving metformin [ 81 ]. The authors concluded that metformin should stay among frontline drugs for treatment of HFrEF patients with DM [ 81 ].…”
Section: Anti-diabetic Drug Categories and Their Action On Oxidative ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, whereas metformin was not independently associated with clinical outcomes in patients with type 2 DM and heart failure with preserved ejection fraction (HFpEF), it was associated with lower all-cause mortality in the subgroup of patients with poor glycemic control [ 80 ]. In a recent report dealing with diabetic patients with advanced heart failure with reduced ejection fraction (HFrEF), patients treated with metformin demonstrated better quality of life and improved outcomes compared with the patients not receiving metformin [ 81 ]. The authors concluded that metformin should stay among frontline drugs for treatment of HFrEF patients with DM [ 81 ].…”
Section: Anti-diabetic Drug Categories and Their Action On Oxidative ...mentioning
confidence: 99%
“…In a recent report dealing with diabetic patients with advanced heart failure with reduced ejection fraction (HFrEF), patients treated with metformin demonstrated better quality of life and improved outcomes compared with the patients not receiving metformin [ 81 ]. The authors concluded that metformin should stay among frontline drugs for treatment of HFrEF patients with DM [ 81 ].…”
Section: Anti-diabetic Drug Categories and Their Action On Oxidative ...mentioning
confidence: 99%
“…Right ventricular dysfunction (RVD) is a major complicating condition of heart failure (HF) with both preserved and reduced EF and is associated with poor prognosis (1)(2)(3). Although no specific RV dysfunction-targeted therapy is currently available, RV dysfunction is commonly present in advanced HF, and may herald clinical worsening with the need of intensification or therapy or timely indication to heart transplantation.…”
Section: Introductionmentioning
confidence: 99%